Investigation into quasi-static and dynamic tensile mechanical properties of aluminium–scandium alloy. Issue 17 (21st November 2020) - Lin, Chi-Feng; Chen, Tao-Hsing; Tsai, Liren; Hsieh, Tsung-Han; Su, Wei-Chih; Wang, I.-Hsin
Abstract : The mechanical properties of aluminium–scandium alloy are investigated at strain rates ranging from 0.0005 to 2600 s −1 and a temperature of 25°C using a material testing system and split-Hopkinson tensile bar. The temperature dependence of the material response is investigated at elevated temperatures of 100 to 300°C under a strain rate of 0.0005 s −1 . The flow stress increases with increasing strain rate but decreases with increasing temperature. The scanning electron microscope observations reveal that the fracture surface contains a large number of dimpled structures with intermetallic precipitates, which suggests a ductile failure mode. Material constants for a combined Johnson-Cook/Cowper-Symonds constitutive model are determined to describe the dynamic behaviours of aluminium–scandium alloys.